Distribution and type of sticky spots at the centre of a deglacial streamlined lobe in northeastern Manitoba, Canada. (20th January 2014) - Trommelen, Michelle S.; Ross, Martin
<x xml:space="preserve">Abstract</x> The distribution of basal drag zones (sticky spots) underneath palaeo‐ice streams or lobes is largely unknown. We investigated the centre of the large (300 km long and up to 400 km wide) deglacial Hayes Lobe in NE Manitoba, Canada, by focusing on surficial till and its composition to get insights into dispersal patterns and their potential relationships to areas of basal drag. Subglacial bed roughness is a good criterion to identify areas of basal drag, but till composition may provide important insights across smoother beds. The onset zone of the Hayes Lobe overlies Palaeozoic Carbonate Platform rocks, whereas the majority of the lobe overlies the low‐lying Canadian Shield. We show that, within a 3500‐km2 central area of this lobe, calcareous detritus within the till has been transported over 100 km within subglacial environments of reduced ice‐bed coupling and fast ice flow. Six per cent of samples (n = 782), however, outline 0.2 to 4 km wide spots with a dominantly local composition. The glacial history and composition indicate that the till within these spots contains high inheritance from a pre‐Late Wisconsinan ice‐flow phase, which we suggest was protected beneath sticky spots (low erosion, high strength) during transport of substantial calcareous detritus to the area. Furthermore, our findings show that local till spots are present within streamlined landforms, as well as till blankets or veneers over bedrock. This diverse geomorphology indicates that the process of drumlinization within the deglacial Hayes Lobe does not appear to have been responsible for significant sediment transport or deposition across the study area. The overall record thus indicates potentially complex spatiotemporal shifts between calcareous till deposition, sticky conditions, erosion and drumlinization – which supports the subglacial bed mosaic model.